A MUSE view of the multiple interacting system HCG 31. Issue 2 (14th April 2023) - Gómez-Espinoza, Diego A; Torres-Flores, S; Firpo, V; Amram, Philippe; Epinat, Benoit; Contini, Thierry; Mendes de Oliveira, Claudia
ABSTRACT: We present, for the first time, spatially resolved spectroscopy for the entire Hickson Compact Group 31 obtained with the MUSE instrument at the VLT and an in-depth analysis of this compact group. To obtain a complete understanding of the system, we derived radial velocity and dispersion velocity maps, maps of the ionization mechanism of the system, chemical abundances and their distribution over the whole system, star formation rates and ages of the different star-forming regions, and the spatial distribution of the Wolf–Rayet stellar population. We also reconstructed the star formation history of the galaxies HCG 31 A, C, B, and F, measured the emission-line fluxes, and performed a stellar population synthesis. Our main findings are: (i) that there is clearly disturbed kinematics due to the merger event that the system is experiencing; (ii) that the ionization is produced exclusively via star formation except for the nucleus of the galaxy HCG 31 A, where there is a small contribution of shocks; (iii) that there is low oxygen abundance distributed homogeneously through the system; (iv) that there is a prominent population of carbon Wolf–Rayet stars in the central zone of the group; and (v) that there are clear evidences of the tidal origin of the galaxies HCG 31 E, HCG 31 H, and HCG 31 F because they show quite high oxygen abundances for their stellar mass. All these findings are clear evidence that HCG 31 is currently in an early merging phase and manifesting a starburst in its central region.